Management of Pseudotumor Cerebri Secondary to Dural Venous Sinus Thrombosis in Children - Mohamed M Elsherbini; Hatem Badr; Mohamed Kassem; Amr Farid Khalil (Brazilian Society for Pediatric Neurosurgery, 2021)
Background: The purpose of this study is to follow the clinical course and required management of children suffering from Pseudotumor cerebri (PTC) secondary to Dural Sinus Thrombosis (DST) to understand the natural history of a rare condition and its need for surgery as well as outcome after Cerebro-Spinal Fluid (CSF) diversion surgeries. Methods: A retrospective consecutive case series study based on examining medical records of patients who were referred to neurosurgical pediatric clinic suffering from PTC secondary to DTS. Data review included patients' archives for clinical, radiological, surgical records and follow up visits. Only patients below 18 years old were included. Results: Fourteen patients met inclusion criteria, 7 of them required CSF diversion procedure, while the other 50% responded to medical conservative therapy. Headache improved immediately for most of the surgical group, while took 7 weeks to reach satisfactory results for medical group. Visual improvement took place for both groups approximately at the same time interval with average 5 weeks. Conclusion: Surgical intervention in the form of CSF diversion procedure was required for 50 % of the patients, which is safe and effective line of treatment to prevent further deterioration of vision for case who were not responsive to medical therapy.